FPolymer: A Program for 3D Structure Generation and OPLS Topology of Polymers with High Molecular Mass - Uliana, Fabricio; da Silva Filho, Eloi Alves; Gonçalves, Arlan da Silva; dos Santos, Vadilson Malaquias; Uliana, Mateus (Orbital: The Electronic Journal of Chemistry, 2022)
The need to study polymeric systems with high molecular masses by techniques such as molecular dynamics using free-use software, coupled with the difficulty of parameterizing such systems, led to the creation of the FPolymer program. This program was built in C++ language using the QT-creator framework and has a simple and intuitive interface. The main function of the program is to use previously parameterized trimers of any polymer to generate a structure with the number of repeating units indicated by the user. As output of the program, the user receives a file .pdb containing the structure of the polymer and a file .top with the topology prepared to perform youngest molecular dynamics in the GROMAS program.DOI: http://dx.doi.org/10.17807/orbital.v14i1.1698